2021
DOI: 10.1021/acs.joc.1c00082
|View full text |Cite
|
Sign up to set email alerts
|

Redox-Neutral 1,3-Dipolar Cycloaddition of 2H-Azirines with 2,4,6-Triarylpyrylium Salts under Visible Light Irradiation

Abstract: A novel visible light mediated redox-neutral 1,3-dipolar cycloaddition of 2H-azirines with 2,4,6-triarylpyrylium tetrafluoroborate salts providing tetrasubstituted pyrroles has been developed. The 2,4,6-triarylpyrylium salt acts as dipolarophile as well as photosensitizer in the reaction, under blue light irradiation. The control experiments indicated single electron oxidation of 2H-azirines by photoexcited pyrylium salts, followed by coupling between an azaallenyl radical cation and triarylpyranyl radical as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…The group of Rastogi [51] demonstrated a visible light mediated redox‐neutral 1,3‐dipolar cycloaddition of 2H ‐azirines with 2,4,6‐triarylpyrylium tetrafluoroborate salts (TPT), serving as dipolarophile as well as photosensitizer (Scheme 30). The proposed mechanism suggested that the reaction proceeded through visible light excitation of TPT to oxidizing TPT* species and single electron oxidation of 2H ‐azirines, followed by radical coupling/1,5‐cyclization/dehydration to provide target products.…”
Section: Reaction Of 2h‐azirinesmentioning
confidence: 99%
“…The group of Rastogi [51] demonstrated a visible light mediated redox‐neutral 1,3‐dipolar cycloaddition of 2H ‐azirines with 2,4,6‐triarylpyrylium tetrafluoroborate salts (TPT), serving as dipolarophile as well as photosensitizer (Scheme 30). The proposed mechanism suggested that the reaction proceeded through visible light excitation of TPT to oxidizing TPT* species and single electron oxidation of 2H ‐azirines, followed by radical coupling/1,5‐cyclization/dehydration to provide target products.…”
Section: Reaction Of 2h‐azirinesmentioning
confidence: 99%
“…Our group recently employed pyrylium salts in a dual role as a photosensitizer and dipolarophile in the dipolar cycloaddition with 2H-azirines for accessing chalcone-bearing tetrasubstituted pyrroles. 10 Herein we present an extension of our previous work 9 utilizing -substituted nitroalkenes as dipolarophiles in organo-photocatalytic formal [3+2] cycloadditions with azirines to prepare tetrasubstituted pyrroles (Scheme 1). -Substituted nitroalkenes can be prepared through the Rauhut-Currier (RC) or Morita-Baylis-Hillman (MBH) reaction of ethyl acrylate, methyl vinyl ketone, or formaldehyde with nitroalkenes.…”
Section: Paper Synopenmentioning
confidence: 99%
“…The 2H-azirines 1a-1d were synthesized from the corresponding ketones by following the standard procedure reported in literature. 10 RC adducts 2 and 3 of nitroalkenes with methyl vinyl ketone and ethyl acrylate, respectively, and MBH adducts 4 of nitroalkenes with formaldehyde were synthesized by following standard protocols reported in the literature. 14 All other chemicals, catalysts, and anhydrous solvents were used as received from commercial sources.…”
Section: Paper Synopenmentioning
confidence: 99%
“…2 H -Azirines are widely used for the preparation of various 4–7-membered N-, N,N-, and N,O-heterocycles of varying degrees of unsaturation and different heteroatom arrangements [ 1 , 2 ]. The ability of azirines to open at any of the three bonds of the ring under the action of electrophilic and nucleophilic reagents, as well as transition metal compounds, underlies a powerful strategy for the synthesis of azete [ 3 ], pyrrole [ 4 , 5 , 6 ], oxazole [ 7 , 8 , 9 ], imidazole [ 10 , 11 , 12 ], 1,2,3-triazole [ 13 ], pyridine [ 14 ] derivatives, and other heterocycles, which are hardly accessible with conventional methods. Some of the azirine-ring opening reactions can be applied for the synthesis of ortho -fused, spiro-fused, and bridged heterocycles.…”
Section: Introductionmentioning
confidence: 99%